2018
DOI: 10.2174/1389201019666180515104800
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity, Gas Chromatographic-Mass Spectrometric Analysis And in silico Study of Punica Granatum Peel Extracts Against Fluconazole Resistant Strains of Candida Species

Abstract: The present study is the first report on the antifungal activity of various extracts of P. granatum against fluconazole resistant Candida isolates. Ethanol extract of P. granatum peel showed excellent anticandidal activity against fluconazole resistant Candida spp. Hence, it can be explored further to identify a potential drug candidate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Butoconazole nitrate, [(±) -1-[4-(p-Chlorophenyl)-2-[2,6-dichlorophenyl) thiol] butyl]-1H-imidazole mononitrate] (III), is an imidazole antifungal; which is primarily used for the local treatment of vulvovaginal candidiasis (infections caused by Candida) [8][9]. Due to the vital importance of these azole antifungals several methods have been reported for the determination of them either in pure forms, dosage forms, or biological fluids like chromatography [10][11][12][13][14][15][16], spectrophotometric [17][18][19][20], electrometric [21][22]. Structure investigation is an important part of drug development due to the need to identify the low level of impurities and degradation of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Butoconazole nitrate, [(±) -1-[4-(p-Chlorophenyl)-2-[2,6-dichlorophenyl) thiol] butyl]-1H-imidazole mononitrate] (III), is an imidazole antifungal; which is primarily used for the local treatment of vulvovaginal candidiasis (infections caused by Candida) [8][9]. Due to the vital importance of these azole antifungals several methods have been reported for the determination of them either in pure forms, dosage forms, or biological fluids like chromatography [10][11][12][13][14][15][16], spectrophotometric [17][18][19][20], electrometric [21][22]. Structure investigation is an important part of drug development due to the need to identify the low level of impurities and degradation of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Several parts of this plant contain numerous phytochemical compounds (flavonoids, polyphenols, tannins, organic acids, etc) [ 15 ]. Recent studies reported innate properties of some phytoextracts from P. granatum , including antioxidant, antiseborrheic, anti-inflammatory, anticarcinogenic, antiviral and antifungal properties [ 15 , 16 , 17 ]. P. granatum extracts have antimicrobial properties in vitro, as demonstrated by the inhibitory effect of an extract on the bacterial growth of S. aureus and Escherichia coli [ 18 ], and multidrug-resistant S. epidermidis strains [ 19 ].…”
Section: Introductionmentioning
confidence: 99%